‘Il limite che mi conteneva nell’ordine’: Emilio Cecchi ‘odeporico’ fra le ere: Messico (1932) - Buzzetti, Rachele (Incontri. Rivista europea di studi italiani, 2023)
Emilio Cecchi (1884-1966) reached the United States in August 1930 as a visiting professor at the University of California, Berkeley. At this occasion, he visited Mexico, passing through Arizona and New Mexico. Out of this experience, Messico (1932) was born. The book is the author’s first literary reportage: a collection of prose texts that had previously been published in the Milanese newspaper Corriere della Sera. This article focuses precisely on the transition from the essay form, which the author had successfully experimented with in his first collection, Pesci rossi (1920), to the literary reportage. It investigates some of the (inter)textual and conceptual characteristics of Messico, as a result of this transition. To begin with, we will look at the influence of Henri Bergson’s theories on time; we will then move on to the importance that essays on film montage had on the prose and structure of Messico; in particular, we will consider the writings of Sergei Michajlovič Ejzenštejn, whom Cecchi knew from his earliest translations. We will then conclude with a reflection on the influence that Carlo Cattaneo, with his essay Gli antichi messicani, had on Cecchi (and on Messico) in terms of method and style.